FUNCTIONS OF THE VILLAGE CONSULTATIVE BODY ON THE IMPLEMENTATION OF VILLAGE GOVERNMENT IN THE PERSPECTIVE OF FIQH SIYASAH - Al Arif, M Yasin; Ariyansyah, Ariyansyah (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2022)
As stated in Article 55 of Law Number 6 of 2014 that the Village Consultative Body has the function of assisting village regulations, accommodating and channeling the aspirations of the Village community and monitoring the performance of the Village Head. This study aims to implement the function of the Village Consultative Body in the Implementation of Village Government which is studied in the perspective of siyasah fiqh. This research is an empirical legal research using primary data which was analyzed descriptively. The results showed that the function of the Village Consultative Body in Talang Batu village had not been running properly, due to the lack of understanding of the members of the Village Consultative Council on the position and authority of the Village Consultative Body. Then in the study of Fiqih Siyasah, the Village Consultative Body as the power of al-sultah al tasyri iyah must be filled by people who understand this power